The association between caregiver burden and behavioral and psychiatric disorders in dementia patients - Nguyen, Le Phi Nguyen; Duong, Thi Thu Huong; Hoang, Tien Trong Nghia; Nguyen, Thi Tien; Phan, Thi Thu Huong (Nursing and Health Sciences Journal (NHSJ), 2026)
Millions of people worldwide have dementia, a progressive loss of cognitive abilities that interferes with day-to-day functioning. Long-term caregiving frequently results in chronic stress and lower care quality, even though caregivers are crucial in addressing daily living and health care needs. Therefore, it is essential to assist caregiver and alleviate their load. This study aimed to quantify caregiver burden and examine its association with behavioral and psychiatric symptoms in dementia. A cross-sectional study was conducted with 94 patient–caregiver pairs from two dementia units. Behavioral and psychiatric symptoms were assessed using the Neuropsychiatric Inventory Questionnaire (NPI-Q), and caregiver burden was measured with the Zarit Burden Interview (ZBI-22). Results showed that 60.6% of caregivers reported burden. Subsequent analysis indicated a statistically significant association (p<0.05) between caregiving burden and several neuropsychiatric symptoms in care recipients, specifically hallucinations (OR = 3.85; 95% CI: 1.45-10.20), delusions (OR = 3.85; 95% CI: 1.45-10.20), motor disturbances (OR = 3.45; 95% CI: 1.38-8.61), irritability (OR = 3.99; 95% CI: 1.62- 9.78), and disinhibition (OR = 3.34; 95% CI: 1.26-8.87). Burden was also higher among caregivers of patients in middle or late stages of dementia (p<0.001), those providing care for longer durations (p<0.05), and those assisting with activities of daily living (p<0.05). In conclusion, caregiver burden is common and strongly related to patients’ behavioral and psychiatric symptoms. The study emphasizes the importance of developing interventions that target these symptoms and providing greater support for caregivers to reduce stress and improve overall care quality. Future research should focus on treatments for specific neuropsychiatric symptoms and on supporting caregivers to reduce their burden.